Toward Greater Transparency and Inclusion in Manuscript Review Processes: A Relational Model - Cook-Sather, Alison; Healey, Ruth L. (Teaching and Learning Inquiry, 2024)
Peer review is widely accepted as critical to legitimating scholarly publication, and yet, it runs the risk of reproducing inequities in publishing processes and products. Acknowledging at once the historical need to legitimize SoTL publications, the current danger of reproducing exclusive practices, and the aspirational goal to “practice what we preach” as SoTL practitioners regarding effective feedback to students, we argue for rethinking “rigor,” developing more inclusive practices, and engaging in greater transparency in relation to peer review. To situate our discussion, we revisit foundational work in the development of SoTL and then offer an analytical framework informed by recent scholarship on redefining rigor and the emotional experience of receiving feedback. Using this framework, we propose a relational model of peer review and present two examples of efforts in which we have been involved as founding co-editors of the International Journal for Students as Partners to move toward greater transparency and inclusion in manuscript review processes. Read the corresponding ISSOTL blog post here.